Development of Laser Rifle Trainer with Full Shot Imitation. (2004) - Bansevicius, Ramutis; Fedaravicius, Algimantas; Ostasevicius, Vytautas; Ragulskis, Minvydas
Abstract : Laser trainers are effective tools for shot and sportsmen training. However, the majority of trainers have neither realistic recoil nor sound imitation systems. The objective of the development of laser rifle trainer with full shot imitation was to investigate and simulate the recoil of combat weapons under single and serial shooting regimes so that the training weapons could simulate complete recoil and sound imitation. Theoretical and experimental investigations lead to the development of shot training systems which were successfully implemented in Lithuanian Army combat training facilities. The laser trainers are also equipped with interactive software interface which does not only control and register the process of shooting but also can reproduce the whole set of statistical data, including psychological impact on the rifleman and detection of his training problems. The incorporation of multimedia advances the system up to interactive laser shot trainer in virtual combat reality.